ANALISIS KESALAHAN BAHASA DALAM PENGGUNAAN KATA KATA DALAM QUOTES DI AKUN SOSIAL MEDIA INSTAGRAM @YOWESSORY - Nur Antonny Priambodo; Bagus Wahyu Setyawan (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2022)
Quotes are citation from a book, movie that contain words of motivation and wisdom for readers. Quotes are usually popular among teenagers to adults, quotes are usually found on social media such as Facebook, Twitter, and what is now popular, Instagram. Quotes are usually given an apostrophe mark (“) to distinguish between quotations and other words, in the manufacture of which the source is usually given. Keywords: Social Media, Instagram, Quotes